PENGARUH PENGETAHUAN, SIKAP, DAN TINDAKAN TERHADAP MASYARAKAT DALAM PEMILIHAN LAYANAN KESEHATAN DI KANAGARIAN KATAPIANG, KABUPATEN PADANG PARIAMAN - Mardelia, Pudja; Hefni; Yanti Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by behavioral factors that have a major influence on the health status of individuals and the community, a high level of education helps increase public knowledge and awareness regarding the importance of public health services, a low level of education will generally give up if they experience health problems. Health behavior can be formulated as all forms of experience and interaction between individuals and their environment, especially those concerning knowledge and attitudes about health, as well as their actions related to health. This study aims to determine the Influence of Knowledge, Attitudes, and Actions on the Community in Choosing Health Services in Kataping Village, Padang Pariaman Regency. In this study, the theory used is the theory of social action proposed by Max Weber. This theory provides a basis for understanding individual and group behavior, recognizing that every action is based on diverse motives and goals. The research method used is quantitative with a descriptive approach, involving data collection through the distribution of questionnaires to 99 respondents who are members of the community in choosing health services in Kanagarian Kataping, Padang Pariaman Regency. The results of the study showed that there was a significant influence between knowledge, attitudes, and actions on community behavior in choosing health services in Kanagarian Kataping, Padang Pariaman Regency. This is evidenced by the results of the T test of 0.002 while the significance of t> 0.05 then Ha is accepted, meaning that there is an influence between knowledge, attitudes, and actions on the community in choosing health services. so that in the service, the level of knowledge of the choice of treatment methods carried out by the community in Kanagarian Katapiang, Padang Pariaman Regency is very influential.